Síntese e caracterização do composto [(Fe(cyclam))2Qz]Cl(PF6)3 para simulação dos complexos formados entre as drogas antraciclinas e os íons FeIII provenientes do organismo - Nascimento, Juliana Sales do (2022)
The cis-[Fe(cyclam)Cl2]Cl (cyclam = 1,4,8,11-tetraazacyclotetradecane) complex reacts with quinizarin (1,4-dihydroxy-9,10-anthraquinone, Qz), a biologically relevant molecule, yielding the binuclear complex [(Fe(cyclam))2(Qz)]Cl(PF6)3. This new compound was characterized by means of elemental analysis, X-ray diffraction, cyclic voltammetry and spectroscopic techniques. Crystallographic and FTIR data indicated that the bridging ligand, quinizarin, is coordinated to the FeIII cation via the oxygen atoms of the carbonyl groups in the form of quinones. The effect of ancillary (cyclam) and bridging (Qz) ligands on the properties of the complex is reflected by the stabilization of the FeIII–FeIII configuration supported by Mössbauer spectroscopy. The efficiency of Oxigen-reactive species generation and DNA cleavage activity for this binuclear complex, as well as for the free quinizarin ligand, were investigated. This metal complex exhibited very low photochemical activity; however, it revealed a great ability to cleave the DNA molecule in the presence of glutathione, which was associated with the production of Oxigen-reactive species species. Thereafter, the cytotoxic activity of these compounds was evaluated using the MTS assay against human tumor cells, namely lung adenocarcinoma (A549) and prostate carcinoma (LNCaP clone FGC), and against normal fibroblasts (L929). Our findings indicated low cytotoxic effects in general, where only a slight reduction in A549 and L929 cell viability was observed after light irradiation. Despite the lack of any significant biological activity, this binuclear compound validates in vitro the essential role of metal binding to an anthracycline-like moiety in the generation of Oxigen-reactive species. The latter may be responsible for some of the cardiotoxicity reported for anthracycline-based drug.